2020
DOI: 10.21475/ajcs.20.14.06.p2524
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of nitrogen fertilizer application to increase growth and yield of rice in ratoon system at tidal swampland

Abstract: This study aims to determine the effect of regulating the provision of nitrogen fertilizer on several rice varieties on the growth and yield of rice in ratoon system at the Tidal swampland. A split plot design was employed in this experiment. The main plot was nitrogen fertilizer application (N) consisting of N1, N2, N3, and N4. The subplot is rice varieties (V) consisting of Inpari 30 (V1), Inpara 3 (V2), Inpari 33 (V3), Inpari 43 (V4) and Hipa 5 Ceva (V5). The results showed that ½ dose nitrogen fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Seeds used in this study are rice hybrid variety (Hipa 5 Ceva) and inbred variety (Inpari 30) in which both are potential to be developed and widely planted by famers at tidal lowland area. Seeds are previously incubated at room temperature in dark condition for 3 days [12] and after germinating they are sown on nursery beds having size of 2 m x 10 m.…”
Section: Plant Materials and Seedling Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds used in this study are rice hybrid variety (Hipa 5 Ceva) and inbred variety (Inpari 30) in which both are potential to be developed and widely planted by famers at tidal lowland area. Seeds are previously incubated at room temperature in dark condition for 3 days [12] and after germinating they are sown on nursery beds having size of 2 m x 10 m.…”
Section: Plant Materials and Seedling Preparationmentioning
confidence: 99%
“…According to [10,11], nitrogen fertilizing gives significant effect on the increase of rice crop production. The study result from [12] showed that nitrogen fertilizing with 1/3 dose given during planting time + 1/3 dose during primordial period + 1/3 dose given at harvest time tend to have good effect on ratoon rice yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N fertilizer management of ratoon rice mainly involves the application of N fertilizer to the main crop and the ratoon crop (bud fertilizer and seedling fertilizer). Many scholars have researched the effects of N fertilizer management in ratoon season on the growth and development of ratoon crops, and most agree that the application of bud and seedling fertilizers can promote the growth of regenerated buds and improve the regenerative capacity and yield of ratoon crops [15,16]. However, there are relatively few studies about the effects of N fertilizer management in the main crop on the growth and development of ratoon crops, and the results have been inconsistent or even contradictory.…”
Section: Introductionmentioning
confidence: 99%